2019
DOI: 10.3389/fimmu.2019.00680
|View full text |Cite
|
Sign up to set email alerts
|

The Pivotal Role of Regulatory T Cells in the Regulation of Innate Immune Cells

Abstract: The distinction between innate and adaptive immunity is one of the basic tenets of immunology. The co-operation between these two arms of the immune system is a major determinant of the resistance or susceptibility of the host following pathogen invasion. Hence, this interactive co-operation between cells of the innate and adaptive immunity is of significant interest to immunologists. The sub-population of CD4 + T cells with regulatory phenotype (regulatory T cells; Tregs), which constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
147
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(151 citation statements)
references
References 181 publications
2
147
0
2
Order By: Relevance
“…Therefore, we undertook a meta-analysis of 22 studies compromising three major types of GCs with 2115 patients to elucidate the clinical implications and prognostic value of Tregs in GCs. Our findings saw a consistent trend of increased frequency of Tregs in both PB and tissues which agreed with the phenomena that elevated accumulation of Tregs had the ability to hamper effective anti-tumor immune responses and maintain immunological tolerance in tumor-bearing hosts via co-operative interaction with certain other immune cells [38,39]. Of interest, frequency of Tregs in tissues was found mildly higher than those in PB (3.47 vs 2.32) for the reason that intra-tumoral Tregs originated primarily from certain kind of PB Tregs which were proved to be inclined to move into the lesion areas with the stimulation of inflammatory factors contributing to the progression of cancers [40].…”
Section: Proportion Of Tregs In Pb Was a Biomarker For Gcssupporting
confidence: 86%
“…Therefore, we undertook a meta-analysis of 22 studies compromising three major types of GCs with 2115 patients to elucidate the clinical implications and prognostic value of Tregs in GCs. Our findings saw a consistent trend of increased frequency of Tregs in both PB and tissues which agreed with the phenomena that elevated accumulation of Tregs had the ability to hamper effective anti-tumor immune responses and maintain immunological tolerance in tumor-bearing hosts via co-operative interaction with certain other immune cells [38,39]. Of interest, frequency of Tregs in tissues was found mildly higher than those in PB (3.47 vs 2.32) for the reason that intra-tumoral Tregs originated primarily from certain kind of PB Tregs which were proved to be inclined to move into the lesion areas with the stimulation of inflammatory factors contributing to the progression of cancers [40].…”
Section: Proportion Of Tregs In Pb Was a Biomarker For Gcssupporting
confidence: 86%
“…In addition to suppressing T cells, Tregs suppress various innate immune cells, including monocytes, via mechanisms which are often distinct from those relevant to T-cell suppression [38,39]. In parallel to suppressing IL-17A, we found that BMS-336 concurrently increased the expression/secretion of IL-10 by Th17-Tregs ( Fig.…”
Section: Rorc2 Inhibition Promotes Th17-tregs To Produce Il-10 and Sumentioning
confidence: 73%
“…In recent years, Tregs have been shown to suppress most immune cell populations, including lymphocytes, various types of macrophages, dendritic cells and B cells (59). Interestingly, the manifestation of Treg suppressive activity against a specific T effector population may be associated with the expression of transcription factors typical of this subpopulation.…”
Section: Treg Suppressive Activity Mechanismsmentioning
confidence: 99%